Collaborative Learning and Its Positive Impact in the Cognitive Development of Children with Learning Disabilities - Skopeliti, Irini; Riga, Asimina (Current Research in Language, Literature and Education Vol. 2, 2021)
The present paper tends to gain a better understanding of the characteristics directly associated with collaborative learning and its role on the cognitive development of students with Learning Disabilities. These students undoubtedly face difficulties in both developing cognitive abilities and acquiring new knowledge. They also live under a constant anxiety related to their behavior refinement, the strengthening of their communication skills and finally the establishment of solid relationships with their surroundings. The aim of the paper is to present the ways that collaborative learning may support students with Learning Disabilities who face the above-mentioned difficulties. This paper further provides the repertoire of the different types of collaborative learning activities, which are considered suitable to serve learning purposes directed to students with impairments. Finally, this paper pinpoints that the use of Information and Communication Technologies and multimedia in collaborative learning environment raise students’ interest in learning and boosts attention span.